A porous silicon-carbon composite material for lithium-ion battery and a preparation method thereof
By adopting a porous silicon-carbon composite material with a three-layer composite capsule structure, spray granulation and HF etching are used to form a porous structure, and the structure problems caused by volume expansion of silicon in lithium-ion batteries are solved, and the circulation performance and capacity of the battery are significantly improved.
Patent Information
- Application Number
- CN202410643608.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-05-23
AI Technical Summary
The volume expansion of the silicon-carbon composite materials used in existing lithium-ion batteries during charging and discharging leads to structural collapse and electrode peeling, affecting the battery circulation performance and capacity.
The porous silicon-carbon composite material with a three-layer composite capsule structure is used to form Si/C/AlF3 composite spherical particles with a porous structure through spray granulation and HF etching, and the porosity is reduced and activated and expanded by carbon-containing porosity, thereby improving the specific surface area and porosity.
The specific surface area and porosity of porous silicon-carbon composite materials have been significantly improved, the circulation performance and charge and discharge capacity of lithium-ion batteries have been improved, the first reversible capacity reaches more than 1300mAh/g, and the first efficiency reaches more than 89%.
Smart Images

Figure CN118610443B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a porous silicon-carbon composite material for lithium-ion batteries and a preparation method thereof. Background Art
[0002] At present, the negative electrode material in the lithium battery industry is mainly graphite, but the theoretical specific capacity of graphite negative electrode is 372mAh / g, while the theoretical specific capacity of silicon can reach 4200mAh / g, the coulomb efficiency is close to that of graphite negative electrode, the voltage platform is slightly higher than that of graphite negative electrode, there is no lithium precipitation during charging and discharging, the safety performance is good, and the earth's reserves are abundant, the price is cheap, and it is environmentally friendly, which has the greatest potential to replace graphite negative electrode. However, the silicon material itself has poor conductivity, and the volume expansion during charging and discharging can be as high as 300%, which leads to the collapse of the material structure and the peeling and powdering of the electrode. Each time charging and discharging forms a new interface, silicon, lithium and electrolyte are continuously consumed, resulting in loss of active materials, sharp reduction of battery capacity and deterioration of cycle performance. In order to reduce the impact of silicon volume expansion during the charge and discharge process on the battery and extend the cycle life, the main method used is to reduce the silicon grain size and perform chemical vapor deposition of silane on porous graphite to obtain silicon graphite of amorphous silicon. However, in order to make the silicon-carbon material have a higher specific capacity, the pore properties of the substrate porous carbon, such as specific surface area and pore size distribution, are required to be higher. Therefore, high requirements are placed on the porous carbon preparation process, and the raw material and manufacturing costs are high.
[0003] CN111755677B discloses a core-shell structure porous silicon negative electrode material for lithium ion batteries and a preparation method thereof. The core layer of the porous silicon negative electrode material comprises nanoporous silicon, graphite and amorphous carbon, and the outer shell is amorphous carbon. Nanoporous silicon is first obtained by wet grinding, then compounded with graphite particles, and then at least one layer of amorphous carbon is covered on the surface of the nanoporous silicon and graphite to obtain a core layer. When the negative electrode material described in the invention is used as a negative electrode active material for lithium ion batteries, the battery capacity can be significantly increased, but the nanosilicon particles are small and easy to agglomerate, and the chemical activity is high, and they are easily oxidized, and the material has a low initial efficiency; carbon materials such as graphite have a small specific surface area, and nanosilicon particles agglomerate between graphite layers and on the surface. The dispersion space provided by the carbon material is limited, and the cycle performance is not significantly improved.
[0004] CN116779816A discloses a porous silicon-carbon composite material and its preparation method. The patent adds high molecular organic matter or organic precursor and monomer to silicon slurry, and carbonizes it after drying to obtain a porous silicon-carbon composite scaffold to improve the material capacity and cycle performance. However, the dispersion uniformity of silicon particles in organic matter is limited, which affects the uniformity of the material; and the upper limit of the solid content of the polymer material is low when it is dispersed in an organic solvent, and the spray drying process is difficult and costly. Summary of the invention
[0005] The purpose of the present invention is to provide a porous silicon-carbon composite material to improve the defect that the silicon-carbon composite material used for lithium-ion batteries in the prior art does not significantly improve the electrochemical performance of lithium-ion batteries.
[0006] The present invention achieves the above object through the following technical solutions:
[0007] A porous silicon-carbon composite material for lithium-ion batteries, which is a three-layer composite capsule structure, which comprises a porous silicon-carbon composite support, nano silicon particles and a carbon coating layer from the inside to the outside; the nano silicon particles are partially or completely attached to the pores of the porous silicon-carbon composite support;
[0008] Among them, the raw materials of the porous silicon-carbon composite support include a porous silicon-carbon composite support precursor, a carbon-containing pore shrinking agent and an activator, and the porous silicon-carbon composite support precursor is pore-shrinking and activated and expanded by the carbon-containing pore shrinking agent and the activator. The carbon-containing pore shrinking agent forms a carbon layer attached to the pores and surface of the porous silicon-carbon composite support precursor; the porous silicon-carbon composite support precursor is a porous structured Si / C / AlF3 composite spherical particle, which is formed by spray granulation of nano-silicon powder, graphite, silica sol and aluminum sol into Si / C / SiO2 / Al(OH)3 composite spherical particles, and then etched by HF; wherein graphite is the skeleton, nano-silicon particles are embedded in it, and AlF3 plays a reinforcing and supporting role.
[0009] The composite spherical particles obtained after spray granulation have a stable structure, but usually have a small specific surface area, limited porosity, and uneven pore size distribution. Therefore, the silicon-carbon composite material formed by spray granulation has limited effect on alleviating the volume expansion of silicon, and affects the uniformity and content of subsequent deposited silicon. The present invention uses a compounded aluminum sol / silicon sol as a binder, and spray granulates to obtain Si / C / SiO2 / Al(OH)3 composite spherical particles; then HF is used for etching, and a large number of pores are generated after SiO2 is etched; Al(OH)3 is converted into AlF3 after etching, and remains in the spherical particles to form Si / C / AlF3 composite spherical particles with a porous structure. Since AlF3 has high mechanical strength and is retained in spherical particles in situ, it can play a reinforcing and supporting role, avoiding structural collapse caused by the generation of pores. The relevant reaction formula is as follows. The SiO2 content in the Si / C / SiO2 / Al(OH)3 composite spherical particles obtained by spray granulation must be within an appropriate range. If the content is too low, the porosity of the Si / C / AlF3 composite spherical particles formed after etching is low, and the corresponding specific surface area is small, which cannot effectively alleviate the volume expansion of silicon; if the content is too high, the Al(OH)3 content is low, and the pore structure of the Si / C / AlF3 composite spherical particles formed is unstable, and structural collapse is prone to occur.
[0010] SiO2+4HF=SiF4↑+2H2O
[0011] Al(OH)3+3HF=AlF3+3H2O
[0012] The porosity and specific area of the Si / C / AlF3 composite spherical particles with a porous structure obtained after spray granulation and etching are significantly improved, but the distribution of the pore size is uneven. The presence of large pores will affect the uniformity and content of deposited silicon. The present invention uses a carbon-containing shrinking agent to shrink its large pores, and then uses an activator to activate and expand the pores as a whole, thereby increasing the number of micro-mesopores and making the pore size distribution more uniform. In summary, the porous silicon-carbon composite material prepared by the present invention through granulation with a composite aluminum sol / silica sol as an adhesive, then etching the composite particles with HF, and then using a carbon-containing shrinking agent and an activator to shrink the pores and activate the pores has abundant pores and a uniform pore size distribution, thereby improving the specific surface area and adsorption capacity, and providing more space for the next step of depositing silicon particles.
[0013] Furthermore, in the porous silicon-carbon composite material, the porous silicon-carbon composite support accounts for 40wt% to 70wt%, the nano-silicon particles account for 15wt% to 35wt%, and the rest is a carbon coating layer; in terms of elements, in the porous silicon-carbon composite material, Si accounts for 35wt% to 80wt%, C accounts for 20wt% to 45wt%, Al accounts for 3wt% to 7wt%, F accounts for 6wt% to 15wt%, and there may be unavoidable impurities, such as O.
[0014] Furthermore, in the porous silicon-carbon composite support, the porous silicon-carbon composite support precursor accounts for 70wt% to 95wt%, and the carbon layer formed by the carbon-containing pore shrinking agent accounts for 5wt% to 30wt%.
[0015] Furthermore, the specific surface area of the porous silicon-carbon composite material is 1 to 10 m 2 / g; the specific surface area of the porous silicon-carbon composite support is 1000 to 2000m 2 / g; the specific surface area of the porous silicon-carbon composite support precursor is 600 to 900m 2 / g, and its particle size D50 is 6 to 20 μm.
[0016] Furthermore, the mass ratio of nano silicon powder, graphite, SiO2 and Al(OH)3 in the Si / C / SiO2 / Al(OH)3 composite spherical particles is 100:(45-65):(15-25):(15-25), preferably 100:(55-65):(20-25):(20-25).
[0017] Furthermore, the graphite is at least one of artificial graphite, natural graphite, and graphitized mesophase carbon microspheres; preferably artificial graphite.
[0018] Furthermore, the particle size D50 of the nano silicon powder is 20-120 nm, the particle size D50 of the graphite is 3-10 μm, the particle size D50 of the aluminum sol is 10-60 nm, and the particle size D50 of the silica sol is 10-60 nm.
[0019] Furthermore, the carbon-containing pore shrinking agent is one or more of glucose, asphalt, epoxy resin, phenolic resin, furfural resin, polyethylene glycol, polyamide resin, and cellulose; the activator is a physical activator or a chemical activator, the physical activator is at least one of water vapor, carbon dioxide, and air, and the chemical activator is at least one of KOH, NaOH, KHCO3, and NaHCO3.
[0020] Nano silicon particles on the porous silicon-carbon composite scaffold can further improve the capacity of the porous silicon-carbon composite material, but its content should not be too high. If the content is too high, there will be more nano silicon particles distributed on the surface of the porous silicon-carbon composite scaffold. When the proportion of the carbon coating layer is low, some silicon nano particles will be exposed, and the exposed silicon nano particles are easily oxidized, and then the capacity, first coulomb efficiency and cycle performance of the lithium battery prepared by the porous silicon-carbon composite material will be affected. Therefore, in the porous silicon-carbon composite material with a three-layer composite capsule structure, the proportion of nano silicon particles and carbon coating layer should be within an appropriate range.
[0021] The silicon element in the porous silicon-carbon composite material comes from the nano-silicon powder in the porous silicon-carbon composite scaffold precursor and the nano-silicon particles on the porous silicon-carbon composite scaffold. Its content should be within a reasonable range. If the content is too low, the capacity of the porous silicon-carbon composite material is low, and if the content is too high, the conductivity of the system is poor. Therefore, the proportion of silicon elements in the porous silicon-carbon composite material should be within a suitable range. As mentioned above, the nano-silicon particles on the porous silicon-carbon composite scaffold should not be too high. In order to achieve the proportion of silicon elements, the proportion of nano-silicon powder in the porous silicon-carbon composite scaffold precursor can be adjusted within a certain range.
[0022] In a second aspect, the present invention provides a method for preparing the aforementioned porous silicon-carbon composite material for lithium-ion batteries, comprising the following steps:
[0023] (S1) adding silicon powder to a solvent and grinding the silicon powder to obtain a nano-silicon slurry in which nano-silicon powder is dispersed in the solvent;
[0024] (S2) adding graphite, silica sol and aluminum sol to the nano-silicon slurry in step (S1) to form a mixed slurry, and then spraying and granulating the mixed slurry to obtain Si / C / SiO2 / Al(OH)3 composite spherical particles; etching, cleaning and drying the composite spherical particles with HF to obtain Si / C / AlF3 composite spherical particles with a porous structure, i.e., a porous silicon-carbon composite scaffold precursor;
[0025] (S3) using a carbon-containing pore shrinking agent and an activating agent to shrink the pores of a porous silicon-carbon composite scaffold precursor and activate and expand the pores to obtain a porous silicon-carbon composite scaffold;
[0026] (S4) using an organic silicon source gas to perform chemical vapor deposition on the porous silicon-carbon composite support, so that part or all of the nano-silicon particles are attached to the pores of the porous silicon-carbon composite support; then using a gaseous carbon source to perform vapor deposition to form a carbon coating layer, thereby obtaining a porous silicon-carbon composite product.
[0027] Furthermore, the solvent in step (S1) is an alcohol solvent or a ketone solvent, the alcohol solvent is selected from C1-3 alcohol; the ketone solvent is selected from C1-3 ketone; the solid content of the nano-silicon slurry is 10% to 30%, and the grinding time is 5 to 30 hours.
[0028] Furthermore, in step (S2), the solid content of the aluminum sol is 20% to 40%, and the solid content of the silica sol is 20% to 40%; the conditions for the spray granulation are: the inlet temperature of the spray dryer is 160 to 300°C, the outlet temperature is 70 to 130°C, and the atomizer speed is 2000 to 4000 rpm.
[0029] Furthermore, the conditions of the HF etching in step (S2) are: 6-12wt% HF solution, etching at 50-60°C for 30-60min, and the amount of HF is 4-10wt% of the Si / C / SiO2 / Al(OH)3 composite spherical particles; the cleaning is centrifugal washing with deionized water for 3-5 times until neutral; and the drying is drying in an oven at 80-100°C for 24-36h.
[0030] Furthermore, in step (S3), the activator is a physical activator or a chemical activator; when a physical activator is used, a shrinking agent is first added to shrink the pores, and then an activator is added to activate and expand the pores; when a chemical activator is used, a carbon-containing shrinking agent and an activator are added together, and shrinking and activating are carried out simultaneously, and washing and drying are required after completion.
[0031] Furthermore, the shrinkage conditions of step (S3) are as follows: after mixing the porous silicon-carbon composite support precursor and the carbon-containing shrinkage agent, carbonizing them at 400-1000°C for 2-5h; the amount of the carbon-containing shrinkage agent is 5-30wt% of the porous silicon-carbon composite support precursor; the activation conditions of step (S3) are as follows: temperature 500°C-1000°C, activation time 0.5h-4h; when the activator is a chemical activator, its amount is 5-20wt% of the porous silicon-carbon composite support precursor.
[0032] Furthermore, in step (S4), the organosilicon source gas is selected from at least one of silane, dichlorosilane, trichlorosilane, silicon tetrachloride, silicon tetrafluoride, disilane, etc.; the usage ratio of the porous silicon-carbon composite support to the organosilicon source gas is 1kg: 120L~250L; the conditions of the chemical vapor deposition are: deposition for 2h~8h under an inert atmosphere at 500℃~900℃, and the inert atmosphere is nitrogen and / or argon and / or helium.
[0033] Furthermore, in step (S4), the gaseous carbon source is selected from at least one of C1-4 alkanes, C2-4 alkenes, and C2-4 alkynes; the usage ratio of the porous silicon-carbon composite support to the gaseous carbon source is 1kg: 250L~500L; the conditions for vapor deposition of the gaseous carbon source to form a carbon coating layer are: reacting for 1h~8h under an inert atmosphere at 400℃~1000℃.
[0034] Furthermore, the chemical vapor deposition and vapor deposition of the gaseous carbon source to form the carbon coating layer in step (S4) are both carried out in a CVD furnace, and the filling volume of the solid material in the furnace accounts for 5-25% of the furnace volume.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1) The present invention uses a compounded aluminum sol / silica sol as a binder, and spray granulation is performed to obtain Si / C / SiO2 / Al(OH)3 composite spherical particles; HF is then used for etching, and a large number of pores are generated after SiO2 is etched; Al(OH)3 is converted into AlF3 after etching, and remains in the spherical particles, forming a porous Si / C / AlF3 spherical particle with a stable structure, and AlF3 plays a reinforcing and supporting role, thereby avoiding structural collapse caused by the generation of pores. The large pores in the porous Si / C / AlF3 spherical particles are then filled and shrunk by a carbon layer formed by a carbon-containing pore shrinking agent, and the pores are expanded by an activator, finally obtaining a porous silicon-carbon composite material with a large specific surface area, high porosity, and uniform pore size distribution, and its specific surface area reaches 1200m 2 / g or above.
[0037] 2) The porous silicon-carbon composite material is used as the negative electrode material of lithium batteries, which can effectively alleviate the volume expansion of silicon and improve the cycle performance and charge and discharge capacity of lithium-ion batteries. Its first reversible capacity is above 1300mAh / g, the first efficiency is above 89%, and the discharge capacity retention rate can still reach above 90% after 100 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the SEM image of the porous silicon-carbon-based composite bracket prepared in Example 1.
[0039] Figure 2This is the SEM image of the porous silicon-carbon-based composite bracket prepared in Comparative Example 1.
[0040] Figure 3 This is the pore size distribution diagram of the porous silicon-carbon-based composite bracket prepared in Example 1.
[0041] Figure 4 This is the pore size distribution diagram of the porous silicon-carbon based composite bracket prepared in Comparative Example 2. DETAILED DESCRIPTION
[0042] In order to better explain the present invention, the following description will be given in detail with reference to the embodiments of the present invention, and the main contents of the present invention will be further clarified in conjunction with specific examples. However, the contents of the present invention are not limited to the following examples.
[0043] Unless otherwise specified, the "parts" in the examples of the present invention are all parts by weight. All reagents used are commercially available reagents in the art.
[0044] The silica sol was selected from SW15-30 / 1 of Zhejiang Delixin Micro-Nano Technology Co., Ltd., with a particle size D50 of 15 nm and a solid content of 30%.
[0045] The aluminum sol was selected from WAL-G1 of Guangzhou Fuer Chemical Technology Co., Ltd., with a particle size D50 of 30 nm and a solid content of 30%.
[0046] The dimensions of the CVD furnace are: 30 cm in diameter and 60 cm in length.
[0047] Example 1
[0048] A porous silicon-carbon composite material for lithium-ion batteries is prepared by a preparation method comprising the following steps:
[0049] (S1) adding 1000 g of silicon powder and 4000 g of isopropanol into a dispersion tank of a sand mill and grinding for 10 h to obtain a nano-silicon slurry in which nano-silicon powder with a particle size D50 of about 100 nm is dispersed in isopropanol;
[0050] (S2) adding 450 g of natural graphite with a particle size D50 of 6.3 μm, 500 g of silica sol with a particle size D50 of 15 nm and a solid content of 30%, and 500 g of aluminum sol with a particle size D50 of 30 nm and a solid content of 30% to the nano-silicon slurry prepared in step (S1), and stirring to form a mixed slurry; granulating the mixed slurry through a rotary spray dryer to obtain Si / C / SiO2 / Al(OH)3 composite spherical particles with a particle size D50 of 15.2 μm (i.e., nano-silicon powder, graphite, SiO2 and Al(OH)3 in the composite spherical particles); The mass ratio of H)3 is 100:45:15:15), the inlet temperature of the rotary spray dryer is 220°C, the outlet temperature is 80°C, and the atomizer speed is 3000r.pm; 500g of Si / C / SiO2 / Al(OH)3 composite spherical particles are taken, and 400g of 10wt% HF solution is used to etch it at 50°C for 30min. After the etching is completed, it is centrifuged and washed 3 times with deionized water, and dried in an oven at 80°C for 24h to obtain Si / C / AlF3 composite spherical particles with a porous structure, that is, a porous silicon-carbon composite bracket precursor;
[0051] (S3) 300 g of the porous silicon-carbon composite scaffold precursor obtained in (S2) and 45 g of asphalt are added to a composite device and mixed for 0.5 h to obtain a mixture, the mixture is placed in a box furnace, the box furnace temperature is increased to 800° C. under a nitrogen atmosphere, and carbonization is performed for 2 h; then the box furnace temperature is maintained, the nitrogen is replaced with water vapor gas to activate and expand the carbonized sample, and after activation for 0.5 h, the water vapor is replaced with nitrogen, the heating is stopped, and the temperature is naturally lowered, and the sample is taken out after the box furnace temperature reaches room temperature to obtain a porous silicon-carbon composite scaffold;
[0052] (S4) placing the porous silicon-carbon-based composite support obtained in step (S3) in a CVD furnace with a rotation speed of 20 rpm, introducing helium at a flow rate of 6 L / min, and heating to 500°C in a helium environment, maintaining the helium flow rate and introducing monosilane gas at a flow rate of 1.5 L / min, and performing chemical vapor deposition for 6 hours, so that the formed silicon particles are partially or completely attached to the pores of the porous silicon-carbon composite support; after the silane deposition is completed, the monosilane gas is stopped, and helium is continuously introduced at a flow rate of 6 L / min to remove excess monosilane gas, and then acetylene gas is introduced at a flow rate of 3 L / min and maintained at 500°C for vapor deposition for 3 hours, and the carbon particles formed after the decomposition of the acetylene gas are deposited on the surface of the silicon particles and the surface of the composite support, i.e., a carbon coating layer is formed, and finally a porous silicon-carbon composite material is obtained.
[0053] The SEM image of the porous silicon-carbon based composite scaffold prepared in Example 1 is as follows: Figure 1 The pore size distribution diagram is shown in Figure 3 shown.
[0054] Example 2
[0055] The rest is the same as Example 1, except that, in step (S2), the amounts of natural graphite, silica sol and alumina sol are: 500 g natural graphite, 500 g silica sol and 667 g alumina sol, that is, the mass ratio of nano-silicon powder, graphite, SiO2 and Al(OH)3 in the composite spherical particles is 100:50:15:20, and Si / C / SiO2 / Al(OH)3 composite spherical particles with a D50 of 14.8 μm are obtained, and finally a porous silicon-carbon composite material is obtained.
[0056] Example 3
[0057] The rest is the same as Example 1, except that, in step (S2), the amounts of natural graphite, aluminum sol and silica sol are: 550 g natural graphite, 667 g silica sol, 833 g aluminum sol, that is, the mass ratio of nano-silicon, graphite, SiO2 and Al(OH)3 in the composite spherical particles is 100:55:20:25, and finally Si / C / SiO2 / Al(OH)3 composite spherical particles with a D50 of 15.1 μm are obtained, and finally a porous silicon-carbon composite material is obtained.
[0058] Example 4
[0059] The rest is the same as Example 1, except that, in step (S2), the amounts of natural graphite, aluminum sol and silica sol are: 600 g natural graphite, 833 g silica sol, 833 g aluminum sol, that is, the mass ratio of nano silicon powder, graphite, SiO2 and Al(OH)3 in the composite spherical particles is 100:60:25:25, and finally Si / C / SiO2 / Al(OH)3 composite spherical particles with D50 of 14.7 μm are obtained, and finally a porous silicon-carbon composite material is obtained.
[0060] Example 5
[0061] The rest is the same as Example 1, except that, in step (S2), the amounts of natural graphite, aluminum sol and silica sol are: 650 g natural graphite, 833 g silica sol, 677 g aluminum sol, that is, the mass ratio of nano silicon powder, graphite, SiO2 and Al(OH)3 in the composite spherical particles is 100:65:25:25, and finally Si / C / SiO2 / Al(OH)3 composite spherical particles with a D50 of 14.7 μm are obtained, and finally a porous silicon-carbon composite material is obtained.
[0062] Example 6
[0063] The rest is the same as Example 1, except that in step (S2), artificial graphite with a particle size D50 of 6.6 μm is used instead of natural graphite to finally obtain a porous silicon-carbon composite material.
[0064] Example 7
[0065] The rest is the same as Example 1, except that step (S3) is:
[0066] Take 300g of the porous silicon-carbon composite support precursor obtained in (S2), 45g of asphalt, and 50g of KOH, add them to the composite equipment and mix for 0.5h to obtain a mixture, place the mixture in a box furnace, raise the temperature of the box furnace to 600℃ under a nitrogen atmosphere and carbonize for 3h; then continue to heat to 800℃ and keep it warm for 2h, cool to room temperature after the insulation is completed, wash with water 3 times until neutral, and dry in an oven at 100℃ for 36h; obtain a porous silicon-carbon composite support.
[0067] Example 8
[0068] The rest is the same as Example 1, except that in step (S2), after spray granulation, the composite spherical particles are etched with HF solution for 15 minutes.
[0069] Comparative Example 1
[0070] The rest is the same as Example 1, except that silica sol is not added in step (S2).
[0071] The SEM image of the porous silicon-carbon based composite scaffold prepared in Comparative Example 1 is as follows: Figure 2 shown.
[0072] Comparative Example 2
[0073] The rest is the same as Example 1, except that step (S3) is omitted, that is, the porous silicon-carbon composite support precursor is directly vapor deposited and coated with a carbon layer without shrinking the pores and activating the pores to expand the pores.
[0074] The pore size distribution diagram of the porous silicon-carbon based composite scaffold prepared in Comparative Example 2 is as follows: Figure 4 shown.
[0075] Application Example 1
[0076] The porous silicon-carbon composite material prepared in Example 1 was applied to the negative electrode of a lithium-ion battery, assembled into a lithium battery, and its electrochemical performance was tested: the prepared porous silicon-carbon composite material, conductive carbon black and LA133 glue were mixed in a mass ratio of 91:3:6 to form a slurry (wherein the solid content of LA133 glue was 5%), the slurry was evenly coated on a copper foil current collector, and vacuum dried for 12 hours to form a negative electrode sheet; the counter electrode was a metal lithium sheet, the diaphragm was Celgard2400, the electrolyte was 1mol / LLiPF6 / EC+DMC+EMC (the volume ratio of EC to DMC to EMD was 1:1:1), and button cells were assembled in an argon atmosphere glove box. The above assembled battery was charged and discharged on a LAND battery tester, with a voltage range of 5mV to 1.5V and a current density of 80mA / g.
[0077] Application Example 2-8
[0078] Other conditions are the same as those in Application Example 1, except that the porous silicon-carbon composite materials are prepared according to Examples 2-8, respectively.
[0079] Comparative Application Example 1-2
[0080] Other conditions are the same as those in Application Example 1, except that the porous silicon-carbon composite materials are prepared according to Comparative Examples 1-2 respectively.
[0081] Testing and analysis
[0082] The porous silicon-carbon composite stents or porous silicon-carbon composite materials of the above-mentioned embodiments and comparative examples were tested by the following test methods, and the data are shown in Table 1.
[0083] Specific surface area and pore size distribution determination: According to the gas adsorption BET method of GB / T 19587-2017, the porous silicon-carbon composite materials prepared in the examples and comparative examples were subjected to low-temperature nitrogen adsorption experiments using a Tristar II 3020 fully automatic specific surface and pore size analyzer produced by Micromeritics Instrument Corporation of the United States to determine their specific surface area, pore size distribution, and pore volume. Figure 3 This is a pore size distribution diagram of the porous silicon-carbon based composite stent prepared in Example 1; Figure 4 This is the pore size distribution diagram of the porous silicon-carbon based composite bracket prepared in Comparative Example 4.
[0084] Main element content: According to GB / T 38823-2020, the vario EL cube element analyzer from Elementar of Germany was used to test the silicon content in the porous silicon-carbon composite material, and the HCS-801 infrared carbon-sulfur analyzer was used to test the carbon content in the porous silicon-carbon composite material.
[0085] Table 1 Tests of porous silicon-carbon composite materials
[0086]
[0087] From the data in Table 1, it can be seen that in Comparative Example 1, only aluminum sol is used as a binder without using silica sol during spray granulation, and the specific surface area of the composite spherical particles formed thereby is relatively low, and its specific surface area does not exceed 600m 2 / g, which is caused by the fact that silica sol is not used in granulation, and the pores formed after etching are small. In the embodiment, the specific surface area of the porous silicon-carbon composite scaffold prepared by the preparation method of the present invention is significantly improved, reaching 1200m 2 / g or more, pore volume is 0.6~0.9cm 3 / g, belonging to micro-mesopores; the specific surface area of the porous silicon-carbon composite scaffold in the preferred embodiment reaches 1600m 2 / g or more. Combined Figure 1 and Figure 2 It can be seen that the porous silicon-carbon composite scaffold spherical particles prepared in Example 1 have a loose and porous surface; while the porous silicon-carbon composite scaffold spherical particles prepared in Comparative Example 1 have almost no pores on the surface, so the specific surface area is relatively low.
[0088] At the same time, by comparing Example 2, and combining Figure 2 and Figure 4 It can be seen that after the pore shrinkage-activation pore expansion process, the pore size distribution uniformity of the porous silicon-carbon composite scaffold is significantly improved.
[0089] In addition, it can be seen from the data of Examples 1-5 that as the SiO2 content in the Si / C / SiO2 / Al(OH)3 composite spherical particles increases, the specific surface area of the porous silicon-carbon composite scaffold increases. This is because the higher the SiO2 content, the more pores the Si / C / SiO2 / Al(OH)3 composite spherical particles leave after HF etching; however, after reaching a certain value, the specific surface area does not increase significantly with the increase in SiO2 content. The possible reason is that after the SiO2 content reaches a certain value, the Si / C / SiO2 / Al(OH)3 composite spherical particles are etched by HF to form Si / C / AlF3 spherical particles, whose pore structure stability deteriorates.
[0090] The batteries assembled in the application example and the comparative application example were subjected to charge and discharge tests on a LAND battery tester, with a voltage range of 5mV to 1.5V and a current density of 80mA / g. The battery performance tests are shown in Table 2.
[0091] Table 2 Electrochemical performance test
[0092]
[0093]
[0094] It can be seen from the data in Table 2 that the porous silicon-carbon composite material prepared by the preparation method of the present invention is used as a negative electrode material for a lithium battery, and the assembled lithium battery has excellent electrochemical performance, with an initial reversible capacity of more than 1300 mAh / g, an initial efficiency of more than 89%, and a discharge capacity retention rate of more than 90% after 100 cycles, indicating that the assembled lithium battery has good cycle stability and charge and discharge capacity.
[0095] In summary, the porous silicon-carbon composite material prepared by the preparation method of the present invention has a large specific surface area and high porosity, with a specific surface area of 1200m 2 / g or more, and the pore size distribution is uniform; the specific surface area of the preferred embodiment is 1600m 2 The porous silicon-carbon composite material prepared by the preparation method of the present invention can be used as a negative electrode material for lithium batteries, effectively alleviating the volume expansion of silicon and improving the cycle performance and charge-discharge capacity of lithium-ion batteries.
[0096] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A porous silicon-carbon composite material for lithium-ion batteries, characterized in that: It is a three-layer composite capsule structure, which includes a porous silicon-carbon composite support, nano silicon particles and a carbon coating layer from the inside to the outside; the nano silicon particles are partially or completely attached to the pores of the porous silicon-carbon composite support; The raw materials of the porous silicon-carbon composite support include a porous silicon-carbon composite support precursor, a carbon-containing pore shrinking agent and an activator, and the porous silicon-carbon composite support precursor is pore-shrinked and activated and expanded by the carbon-containing pore shrinking agent and the activator, and the carbon-containing pore shrinking agent forms a carbon layer attached to the pores and surface of the porous silicon-carbon composite support precursor; The porous silicon-carbon composite support precursor is a porous Si / C / AlF3 composite spherical particle, which is formed by spray granulation of nano silicon powder, graphite, silica sol and aluminum sol into Si / C / SiO2 / Al(OH)3 composite spherical particles, and then etched by HF; wherein the graphite is the skeleton, the nano silicon particles are embedded in it, and AlF3 plays a reinforcing and supporting role; In the porous silicon-carbon composite material, the porous silicon-carbon composite support accounts for 40wt% to 70wt%, the nano-silicon particles account for 15wt% to 35wt%, and the rest is a carbon coating layer; The mass ratio of nano silicon powder, graphite, SiO2 and Al(OH)3 in the Si / C / SiO2 / Al(OH)3 composite spherical particles is 100:(45-65):(15-25):(15-25).
2. The porous silicon-carbon composite material according to claim 1, characterized in that: According to the elements, in the porous silicon-carbon composite material, Si accounts for 35wt%~80wt%, C accounts for 20wt%~45wt%, Al accounts for 3wt%~7wt%, and F accounts for 6wt%~15wt%; In the porous silicon-carbon composite support, the porous silicon-carbon composite support precursor accounts for 70wt% to 95wt%, and the carbon layer formed by the carbon-containing pore shrinking agent accounts for 5wt% to 30wt%; The specific surface area of the porous silicon-carbon composite material is 1 to 10 m 2 / g; the specific surface area of the porous silicon-carbon composite support is 1000~2000m 2 / g; the specific surface area of the porous silicon-carbon composite support precursor is 600~900m 2 / g, and its particle size D50 is 6~20μm.
3. The porous silicon-carbon composite material according to claim 1, characterized in that: The mass ratio of nano silicon powder, graphite, SiO2 and Al(OH)3 in the Si / C / SiO2 / Al(OH)3 composite spherical particles is 100:(55-65):(20-25):(20-25).
4. The porous silicon-carbon composite material according to claim 1, characterized in that: The graphite is at least one of artificial graphite, natural graphite, and graphitized mesophase carbon microspheres; the particle size D50 of the nano silicon powder is 20-120 nm, the particle size D50 of the graphite is 3-10 μm, the particle size D50 of the aluminum sol is 10-60 nm, and the particle size D50 of the silica sol is 10-60 nm.
5. The porous silicon-carbon composite material according to claim 1, characterized in that: The graphite is artificial graphite.
6. The porous silicon-carbon composite material according to claim 1, characterized in that: The carbon-containing pore shrinking agent is one or more of glucose, asphalt, epoxy resin, phenolic resin, furfural resin, polyethylene glycol, polyamide resin, and cellulose; the activator is a physical activator or a chemical activator, the physical activator is at least one of water vapor, carbon dioxide, and air, and the chemical activator is at least one of KOH, NaOH, KHCO3, and NaHCO3.
7. The method for preparing the porous silicon-carbon composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (S1) adding silicon powder into a solvent and grinding the mixture to obtain a nano-silicon slurry in which nano-silicon powder is dispersed in the solvent; (S2) adding graphite, silica sol and aluminum sol to the nano-silicon slurry in step (S1) to form a mixed slurry, and then spraying and granulating the mixed slurry to obtain Si / C / SiO2 / Al(OH)3 composite spherical particles; then etching, cleaning and drying the composite spherical particles with HF to obtain Si / C / AlF3 composite spherical particles with a porous structure, i.e., a porous silicon-carbon composite scaffold precursor; (S3) using a carbon-containing pore shrinking agent and an activating agent to shrink the pores of a porous silicon-carbon composite scaffold precursor and activate and expand the pores to obtain a porous silicon-carbon composite scaffold; (S4) Chemical vapor deposition is performed on the porous silicon-carbon composite support using an organic silicon source gas, so that part or all of the nano-silicon particles are attached to the pores of the porous silicon-carbon composite support; then, a gas-phase carbon source is used for vapor deposition to form a carbon coating layer, thereby obtaining a porous silicon-carbon composite material.
8. The preparation method according to claim 7, characterized in that: In step (S1), the solvent is an alcohol solvent or a ketone solvent, the alcohol solvent is selected from C1-3 alcohol; the ketone solvent is selected from C1-3 ketone; the solid content of the nano-silicon slurry is 10% to 30%, and the grinding time is 5 to 30 hours.
9. The preparation method according to claim 7, characterized in that: The solid content of the aluminum sol in step (S2) is 20%-40%, and the solid content of the silica sol is 20%-40%; the conditions of the spray granulation are: the inlet temperature of the spray dryer is 160-300°C, the outlet temperature is 70-130°C, and the atomizer speed is 2000-4000 rpm; the conditions of the HF etching are: 6-12wt% HF solution, etching at 50-60°C for 30-60min, and the amount of HF is 4-10wt% of the Si / C / SiO2 / Al(OH)3 composite spherical particles; the cleaning is centrifugal washing with deionized water for 3-5 times until neutral; the drying is drying in an oven at 80-100°C for 24-36h.
10. The preparation method according to claim 7, characterized in that: The shrinkage conditions of step (S3) are as follows: after mixing the porous silicon-carbon composite support precursor and the carbon-containing shrinkage agent, carbonize them at 400-1000°C for 2-5h, and the amount of the carbon-containing shrinkage agent is 5-30wt% of the porous silicon-carbon composite support precursor; the activation and pore expansion conditions of step (S3) are as follows: temperature 500-1000°C, activation time 0.5h-4h; when the activator is a chemical activator, its amount is 5-20wt% of the porous silicon-carbon composite support precursor.
11. The preparation method according to claim 7, characterized in that: In step (S4), the organic silicon source gas is selected from at least one of silane, dichlorodihydrosilane, trichlorosilane, silicon tetrachloride, silicon tetrafluoride, and disilane, and the ratio of the porous silicon-carbon composite support to the organic silicon source gas is 1kg: 120L~250L. The conditions for the chemical vapor deposition are: deposition for 2h~8h under an inert atmosphere of 500℃~900℃, and the inert atmosphere is nitrogen and / or argon and / or helium; in step (S4), the gaseous carbon source is selected from at least one of C1-4 alkanes, C2-4 alkenes, and C2-4 alkynes. The ratio of the porous silicon-carbon composite support to the gaseous carbon source is 1kg: 250L~500L, and the conditions for the gaseous carbon source to be vapor-deposited to form a carbon coating layer are: reaction for 1h~8h under an inert atmosphere of 400℃~1000℃.
Citation Information
Patent Citations
Silicon-carbon composite material for lithium ion battery, preparation method and application of silicon-carbon composite material
CN104716312A
Silicon-carbon composite material, preparation method thereof, battery and application
CN117790753A